Quantification of sulphide oxidation rates in marine sediment. (1st July 2020) - Findlay, Alyssa J.; Pellerin, André; Laufer, Katja; Jørgensen, Bo Barker
Abstract: The marine sulphur cycle is driven by the reduction of sulphate to sulphide coupled to microbial decomposition of organic matter. The sulphide produced by sulphate reduction may either react with Fe or organic matter to be buried as pyrite or organic sulphur, respectively; or may be oxidised through different pathways and intermediates. The amount of sulphide that is oxidised in marine sediments is not well constrained, yet oxidative sulphur cycling has critical implications for hypoxic coastal waters and oxygen minimum zones, carbon mineralisation, microbial metabolism and the interpretation of ancient and modern stable isotope signatures. Here, we present an experimental method to directly determine sulphide oxidation rates in undiluted marine sediment incubations. We find that sulphide oxidation rates in the top two centimetres of organic-rich coastal sediments were greater than rates of sulphide production through sulphate reduction and calculate that in the top 6 centimetres, up to 92 % of sulphide produced during sulphate reduction was reoxidised. The rates decreased steeply with depth, however, and sulphide oxidation to sulphate could no longer be quantified 10 cm below the seafloor. Fe oxides were the primary oxidant for sulphide and the sulphide oxidation rate was related to the amount and reactivity of the Fe minerals. These results provide important insights into the magnitude and processes of the sulphur cycle in marine sediments.